PENJAMINAN HAK-HAK PEREMPUAN DALAM VISI SAUDI ARABIA 2030 - Mega Hardiyanti; Sri Yuniati (Journal of Feminism and Gender Studies, 2021)
Saudi Arabia ia a one of country that has a very high level of gender disparity. Therefore, King Salman made a step in economic reform to make the Saudi State more modern. This economic reform is called Vision Saudi Arabia 2030. One of target Vision Saudi Arabia 2030 is to include women in the development process. Presence of Vision Saudi Arabia in 2030 provides for some women's rights that did not yet exist and were prohibited. Women's rights that are enforced include women's rights in public and political life, right to participate in sports and physical education, women's rights in the field of labor, and women's rights in the economic and social fields by providing facilities and making rules that liberate women. Based on the summary, the concept for this paper is Theory Feminist Liberal.